Review of genotyping methods for Yersinia pestis in Madagascar. - Lovasoa Nomena Randriantseheno; Voahangy Andrianaivoarimanana; Javier Pizarro-Cerdá; David M Wagner; Minoarisoa Rajerison (Public Library of Science (PLoS), 2024)
Background Plague, a zoonotic disease caused by Yersinia pestis, was responsible for 3 historical human pandemics that killed millions of people. It remains endemic in rodent populations in Africa, Asia, North America, and South America but human plague is rare in most of these locations. However, human plague is still highly prevalent in Madagascar, which typically records a significant part of all annual global cases. This has afforded an opportunity to study contemporary human plague in detail using various typing methods for Y. pestis. Aim This review aims to summarize the methods that have been used to type Y. pestis in Madagascar along with the major discoveries that have been made using these approaches. Methods Pubmed and Google Scholar were used to search for the keywords: "typing Yersinia pestis Madagascar," "evolution Yersinia pestis Madagascar," and "diversity Yersinia pestis Madagascar." Eleven publications were relevant to our topic and further information was retrieved from references cited in those publications. Results The history of Y. pestis typing in Madagascar can be divided in 2 periods: the pre-genomics and genomics eras. During the pre-genomics era, ribotyping, direct observation of plasmid content and plasmid restriction fragment length polymorphisms (RFLP) were employed but only revealed a limited amount of diversity among Malagasy Y. pestis strains. Extensive diversity only started to be revealed in the genomics era with the use of clustered regularly interspaced palindromic repeats (CRISPR), multiple-locus variable number tandem repeats (VNTR) analysis (MLVA), and single-nucleotide polymorphisms (SNPs) discovered from whole genome sequences. These higher-resolution genotyping methods have made it possible to highlight the distribution and persistence of genotypes in the different plague foci of Madagascar (Mahajanga and the Central and Northern Highlands) by genotyping strains from the same locations across years, to detect transfers between foci, to date the emergence of genotypes, and even to document the transmission of antimicrobial resistant (AMR) strains during a pneumonic plague outbreak. Despite these discoveries, there still remain topics that deserve to be explored, such as the contribution of horizontal gene transfer to the evolution of Malagasy Y. pestis strains and the evolutionary history of Y. pestis in Madagascar. Conclusions Genotyping of Y. pestis has yielded important insights on plague in Madagascar, particularly since the advent of whole-genome sequencing (WGS). These include a better understanding of plague persistence in the environment, antimicrobial AMR and multi-drug resistance in Y. pestis, and the person-to-person spread of pneumonic plague. Considering that human plague is still a significant public health threat in Madagascar, these insights can be useful for controlling and preventing human plague in Madagascar and elsewhere, and also are relevant for understanding the historical pandemics and the possible use of Y. pestis as a biological weapon.